The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/s1678-9946202163065
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary functional assessment: longitudinal study after treatment of pulmonary tuberculosis

Abstract: Even when treated adequately, pulmonary tuberculosis can lead to pulmonary sequelae. Patients treated for PTB between 2012 and 2016 answered a standardized questionnaire and underwent chest radiography and spirometry, measurement of absolute pulmonary volume, Diffusing Capacity for Carbon Monoxide (DLCO) and the 6-min walk test (6MWT) on two occasions: within the first year after the end of treatment (follow-up 1), and one and two years after follow-up 1 (follow-up 2). A total of 55 patients they underwent spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Impaired DL CO was associated with an increasing number of bronchiectatic lobes 20 . The mean value of DL CO in patients with pulmonary sequelae of tuberculosis was 74.1–78.8% 21 , 22 . Therefore, it would be better to understand the natural course of COPD with heterogeneous features by using DL CO as a holistic index of parenchymal destruction rather than the extent of emphysema.…”
Section: Discussionmentioning
confidence: 93%
“…Impaired DL CO was associated with an increasing number of bronchiectatic lobes 20 . The mean value of DL CO in patients with pulmonary sequelae of tuberculosis was 74.1–78.8% 21 , 22 . Therefore, it would be better to understand the natural course of COPD with heterogeneous features by using DL CO as a holistic index of parenchymal destruction rather than the extent of emphysema.…”
Section: Discussionmentioning
confidence: 93%
“…China’s tuberculosis control program has been implemented for many years, and a large number of TB patients have been discovered and treated, which effectively curbed the trend of tuberculosis transmission. 23 However, due to the non-standard use of anti-tuberculosis drugs, there have been more and more drug resistant tuberculosis cases in China. 23 A previous study showed that China had 120 thousand new cases of MDR-TB annually, accounting for a quarter all over the world.…”
Section: Discussionmentioning
confidence: 99%
“… 23 However, due to the non-standard use of anti-tuberculosis drugs, there have been more and more drug resistant tuberculosis cases in China. 23 A previous study showed that China had 120 thousand new cases of MDR-TB annually, accounting for a quarter all over the world. 24 At present, the pathogenesis of MDR-TB is not clear, and risk factors affecting the occurrence of MDR-TB are varied in different countries and regions.…”
Section: Discussionmentioning
confidence: 99%